Pengembangan Media Pembelajaran Surprise Box Pada Materi Sistem Reproduksi Kelas IX SMPN Satap Katumbangan - Nur Adina Rizal; Dahlia Patiung; Ainul Uyuni Taufiq; Ummul Hasanah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
This development research aims to determine the level of validity, practicality, and effectiveness of Surprise Box learning media on the reproductive system material of class IX SMPN Satap Katumbangan. This research and development (R & D) referred to a 4-D development model consisting of four stages; define, design, develop, and disseminate. The subjects of this study were 13 students in class IX of SMPN Satap Katumbangan. The instruments in this study were literacy sheets, validation sheets, questionnaires, and learning outcomes tests. The media validation result is 3.8, which puts it in the